PENGARUH DOSIS DAN INTERVAL WAKTU PEMBERIAN PUPUK ORGANIK CAIR BMW TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SAWI (Brassica juncea L.) - Ogianto Rajak; Jopi R Patty; Jeanne I Nendissa (Universitas Pattimura, 2016)
The objective of this research was to determine the appropriate dose and application interval of BMW liquid organic fertilizer (POC) to support the growth and yield of vegetative mustard (Brassica juncea L.). This research was conducted in Wailete Village, Hatiwe Besar, Teluk Ambon, Ambon, Maluku Province, from March to April 2016. This research used a Randomized Factorial experimental design with two factors. Factor I was BMW fertilizer dose with 4 levels (P), consisting of: P0 (control), P1 (2.5 mL per liter of water), P2 (5 mL per liter of water) and P3 (7.5 mL per liter of water ). Factor II was interval of spraying (A) consisting of: A1 (6 days), A2 (8 days) and A3 (10 days). There were 12 treatment combinations with three replications, therefore the were 36 experimental plots. Each plot consisted of 28 plants, so that overall there were 1,008 plants. Four plant samples were taken per plot, so that overall there were 114 plant samples. The research results showed that the dose of BMW POC liquid organc fertilizer gave very significant effects on leaf number, leaf area, fresh weight, dry weight and a significant effect on yield per plot. The P3 treatment (7.5 ml per liter of water) gave the best results compared to P0 treatment (without BMW POC). For application interval, it is shown that (the inverval of 6 days) caused a significantly different leaf number of mustard at age 2 weeks after planting, but gave no significant effect on other observation variables. Similarly, the interaction between the dose and application interval of BMW POC did not significantly affect all observation variables.